2018
DOI: 10.3892/mmr.2018.9001
|View full text |Cite
|
Sign up to set email alerts
|

Repair of urethral defects by an adipose mesenchymal stem cell‑porous silk fibroin material

Abstract: The aim of the present study was to determine whether it was possible to repair urethral defects with a material of adipose mesenchymal stem cells (ADMSCs)-porous silk fibroin (SF). A total of 39 male New Zealand white rabbits were randomly divided into a control group, an SF group and a bromodeoxyuridine (BrdU)-labeled ADMSCs-SF group (SSF group; n=13/group). Defects were made by resecting the posterior urethral wall. The defects in the SF and SSF groups were repaired using SF and BrdU-labeled ADMSCs-SF mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Biofunctional films (BFFs) with adjustable ductility and porous structure are useful in many applications, including medicine, sensing, , and tissue engineering . Tunable ductility is necessary for materials where forces from different directions are applied to these BFFs, and pore size as well as porosity of BFFs in cell culture and tissue engineering can have a significant impact on nutrient transport, which influences cell expansion and migration on the films. , Various synthetic materials including poly­(lactic- co -glycolic acid), poly­(methyl methacrylate), and poly­(vinyl alcohol) have been used to prepare BFFs with favorable mechanical properties, but these materials displayed either a lack of biodegradability or irritant degradation products . Hence, natural materials, such as collagen, gelatin, and silk fibroin (SF), have been investigated as candidates for tissue replacements. However, collagen- and gelatin-based materials have excellent biological features but insufficient mechanical toughness, elasticity, and inadequate long-term stability unless additional cross-linking was applied. , SF has excellent inherent properties including biocompatibility, biodegradability, minimal toxicity and irritability, and tunable and robust mechanical properties, and can also be easily cast into films with superior permeability to dissolve oxygen in solution. , , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofunctional films (BFFs) with adjustable ductility and porous structure are useful in many applications, including medicine, sensing, , and tissue engineering . Tunable ductility is necessary for materials where forces from different directions are applied to these BFFs, and pore size as well as porosity of BFFs in cell culture and tissue engineering can have a significant impact on nutrient transport, which influences cell expansion and migration on the films. , Various synthetic materials including poly­(lactic- co -glycolic acid), poly­(methyl methacrylate), and poly­(vinyl alcohol) have been used to prepare BFFs with favorable mechanical properties, but these materials displayed either a lack of biodegradability or irritant degradation products . Hence, natural materials, such as collagen, gelatin, and silk fibroin (SF), have been investigated as candidates for tissue replacements. However, collagen- and gelatin-based materials have excellent biological features but insufficient mechanical toughness, elasticity, and inadequate long-term stability unless additional cross-linking was applied. , SF has excellent inherent properties including biocompatibility, biodegradability, minimal toxicity and irritability, and tunable and robust mechanical properties, and can also be easily cast into films with superior permeability to dissolve oxygen in solution. , , …”
Section: Introductionmentioning
confidence: 99%
“…4 Tunable ductility is necessary for materials where forces from different directions are applied to these BFFs, 5 and pore size as well as porosity of BFFs in cell culture and tissue engineering can have a significant impact on nutrient transport, 6 which influences cell expansion and migration on the films. 7,8 Various synthetic materials including poly(lactic-co-glycolic acid), poly(methyl methacrylate), and poly(vinyl alcohol) have been used to prepare BFFs with favorable mechanical properties, but these materials displayed either a lack of biodegradability or irritant degradation products. 9 Hence, natural materials, such as collagen, gelatin, and silk fibroin (SF), have been investigated as candidates for tissue replacements.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, ECM can provide an ideal microenvironment to accelerate circulation and exchange of oxygen and nutrient between cells and external environment. As a natural scaffold material, previous studies showed that silk fibroin could be shaped into a sheet or film to support the formation of epithelium and displayed significant advantages, including biocompatibility, moderate mechanical, properties and low cost [33][34][35]. However, like any other nonautologous biomaterials, silk fibroin can induce some adverse immunological events for its nonmammalian origin.…”
mentioning
confidence: 99%
“…In such situation, seeding of biomaterials with smooth muscle cells or its progenitors would be desirable. It was also shown in another study that incorporation of mesenchymal stem cells with silk fibroin; compared to acellular silk fibroin, reduces the inflammatory reaction caused by the biomaterial and resulted in better epithelial and smooth muscle growth in the urethral defect [50]. As of the application of naturally derived scaffolds in urologic studies, Pinnagoda et al [38] reported a research in 2016 in which a 2 cm urethral defect was treated with acellular tubular graft, which was made from collagen.…”
Section: Naturally Derived Scaffoldsmentioning
confidence: 99%